Discovery and biosynthesis of macrophasetins from the plant pathogen fungus Macrophomina phaseolina - Yu, Cui; Chen, Lin; Gao, Yang Le; Liu, Jia; Li, Pei Lin; Zhang, Ming Liang; Li, Qin; Zhang, Huai Dong; Tang, Man Cheng; Li, Li (Frontiers in Microbiology, 2022)
3-Decalinoyltetramic acids (DTAs) are a class of natural products with chemical diversity and potent bioactivities. In fungal species there is a general biosynthetic route to synthesize this type of compounds, which usually features a polyketide synthase-nonribosomal peptide synthetase (PKS-NRPS) and a lipocalin-like Diels-Alderase (LLDAse). Using a synthetic biology approach, combining the bioinformatics analysis prediction and heterologous expression, we mined a PKS-NRPS and LLDAse encoding gene cluster from the plant pathogenic fungus Macrophomina phaseolina and characterized the cluster to be responsible for the biosynthesis of novel DTAs, macrophasetins. In addition, we investigated the biosynthesis of these compounds and validated the accuracy of the phylogeny-guided bioinformatics analysis prediction. Our results provided a proof of concept example to this approach, which may facilitate the discovery of novel DTAs from the fungal kingdom.